Designing and Validating an Instrument to Assess Home Literacy Environment in Early Childhood: A Confirmatory Factor Analysis - Maya Oktaviani; Elmanora Elmanora; Mirdat Silitonga; Nurlaila A Mashabi; Eka Nur Pebriyanti Muchtar; Lu'lu' Wal Marjan (Malikussaleh University, Aceh, Indonesia, 2025)
Strengthening literacy from preschool age impacts children's social, emotional, and critical thinking development. This activity aligns with the Sustainable Development Goals, particularly SDG 4, which targets quality and inclusive education for all children. In early literacy development in preschool-aged children, the environment closest to them plays a significant role: the family and school. Therefore, this study aims to develop a Home Literacy Environment (HLE) instrument for preschool-aged children using Confirmatory Factor Analysis (CFA). The study employs a research and development methodology, specifically the 4D model (Define, Design, Develop, Disseminate), to produce a standardized measurement tool. Validation procedures were conducted in three stages: construct validation by three experts, content validation by 14 panellists, and empirical testing involving 165 families with children aged 5–6 years in the Greater Jakarta area. Data were analyzed using CFA to examine factor structure and construct validity. Results indicated that 20 items across the three core dimensions demonstrated adequate factor loadings and significant t-values, with high construct reliability and variance extracted, confirming their validity. Nine indicators of goodness of fit met the criteria. Overall, the model was deemed sufficiently fit and suitable for further interpretation. This study supports the broad applicability of the HLE as a valid measure of the literacy environment created at home for preschool children. By providing a validated HLE instrument, educators, researchers, and policymakers are equipped to assess and enhance the literacy support provided at home. This result enables targeted interventions and informed decision-making to strengthen early learning foundations and promote inclusive, equitable education from the earliest years.